2018
DOI: 10.1021/acssuschemeng.7b04685
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Valorization of 5-Hydroxymethylfurfural and Glycerol into Valuable Diol Monomers with Solid Acid Catalysts

Abstract: Biomass platform molecules such as glycerol and 5-hydroxymethylfurfural have been valorized into diol monomers by acetalization reaction in the presence of tridirectional large pore zeolites (HY and Beta), a laminar zeolite (ITQ-2) and a mesoporous aluminosilicate (MCM-41) and a conventional homogeneous acid catalyst (p-toluenesulfonic acid). The influence of the solvent polarity, pore structure, hydrophobic character and acidity of the catalyst on the activity and selectivity to HMF glyceryl acetals has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 26 publications
2
50
0
Order By: Relevance
“…[17] Therefore, we have first explored here the possibility to produce glyceryl acetals of 5-alkyloxymethyfurfural (2)i no ne pot, by combining the acetalization step of HMFw ith glycerol followed by etherification of the free hydroxymethyl group with af atty alcohol in the presenceo fI TQ-2 zeolite (Scheme 2). [17] Therefore, we have first explored here the possibility to produce glyceryl acetals of 5-alkyloxymethyfurfural (2)i no ne pot, by combining the acetalization step of HMFw ith glycerol followed by etherification of the free hydroxymethyl group with af atty alcohol in the presenceo fI TQ-2 zeolite (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[17] Therefore, we have first explored here the possibility to produce glyceryl acetals of 5-alkyloxymethyfurfural (2)i no ne pot, by combining the acetalization step of HMFw ith glycerol followed by etherification of the free hydroxymethyl group with af atty alcohol in the presenceo fI TQ-2 zeolite (Scheme 2). [17] Therefore, we have first explored here the possibility to produce glyceryl acetals of 5-alkyloxymethyfurfural (2)i no ne pot, by combining the acetalization step of HMFw ith glycerol followed by etherification of the free hydroxymethyl group with af atty alcohol in the presenceo fI TQ-2 zeolite (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…Recently,wereported that the two-dimensional (2D) ITQ-2 zeolite, prepared by delamination of al aminarp recursor of the MWW zeolite, was an excellent catalystf or performing the acetalization of HMF with glycerol, giving the corresponding 1,3dioxolane and 1,3-dioxanes as useful diol monomers. [17] Therefore, we have first explored here the possibility to produce glyceryl acetals of 5-alkyloxymethyfurfural (2)i no ne pot, by combining the acetalization step of HMFw ith glycerol followed by etherification of the free hydroxymethyl group with af atty alcohol in the presenceo fI TQ-2 zeolite (Scheme 2). However,w ec onsidered that this reactions equence could be problematic owing to the inherent reactivityo fa cetals in the presence of water or alcohols, whichc ould lead to the acetal hydrolysiso rt ransacetalization reaction, respectively.N evertheless, the preparation of (2-(5-(octyloxymethyl)furan-2-yl)-1,3-dioxolan-4-yl)methanol( 2a)a nd 2-(5-(octyloxymethyl)furan-2-yl)-1,3-dioxan-5-ol (2b;denoted as 5-(octyloxymethylfurfural) glyceryl acetals, 2), directly from HMF,g lycerol, and octanol according to Scheme 2, was attempted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arias et al [107] valorized glycerol and 5-hydroxymethylfurfural by acetalization reaction in the presence of large pore zeolites HY and Beta, a laminar zeolite ITQ-2, a mesoporous aluminosilicate (MCM-41), and p-toluenesulfonic acid. The research team showed that the homogeneous catalyst mainly promotes polymerization reactions, while HY and Beta are more active catalysts but are less selective and deactivate more rapidly than mesoporous MCM-41 and ITQ-2, whose balance between number of acid sites and adequate surface polarity provides high yield (98%) and selectivity (100%) to the acetals.…”
Section: Heterogeneous Catalysts For Glycerol Acetalizationmentioning
confidence: 99%
“…The acetalization of HMF with glycerol was performed by means of solid acid catalysis, yielding a mixture of 1,3-dioxolane 105 and 1,3-dioxane 106 (Scheme 41). [120][121] The acetalization with glycerol was extended to several in situ formed 5-(alkyloxymethyl)furfurals for the preparation of potential surfactant molecules 107 and 108 in a one-pot process. [122] The resulting compounds with HLB values in the range of 4.9 to 6.6 and good thermal and water stability could be useful for industrial applications as W/O emulsifiers.…”
Section: Carbon-oxygen and Carbon-sulfur Bond Formation Reactionsmentioning
confidence: 99%